2022
DOI: 10.1183/16000617.0039-2022
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for asthma exacerbations during pregnancy: a systematic review and meta-analysis

Abstract: BackgroundConflicting literature exists regarding the risk factors for exacerbations among pregnant women with asthma. This systematic review and meta-analysis aimed to determine risk factors for asthma exacerbations during pregnancy.MethodsElectronic databases were searched for the following terms: (asthma or wheeze) and (pregnan* or perinat* or obstet*) and (exacerb* or flare up or morbidit* or attack*).All studies published between 2000 and 24 August 2021 were considered for inclusion if they reported at le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 73 publications
0
7
0
2
Order By: Relevance
“…A recent meta-analysis of 35 publications involving 429 583 pregnant women identified several important risk factors for asthma exacerbations during pregnancy [14 ▪▪ ]. The authors found that increased maternal age (mean difference 0.62, 95% CI 0.11–1.13), obesity (relative risk 1.25, 95% CI 1.15–1.37), smoking (relative risk 1.35, 95% CI 1.04–1.75), black ethnicity (relative risk 1.62, 95% CI 1.52–1.73), multiparity (relative risk 1.31, 95% CI 1.01–1.68), depression/anxiety (relative risk 1.42, 95% CI 1.27–1.59), moderate–severe asthma (relative risk 3.44, 95% CI 2.03–5.83, versus mild) and severe asthma (relative risk 2.70, 95% CI 1.85–3.95) were associated with an increased risk of asthma exacerbations during pregnancy.…”
Section: Risk Factors During Pregnancymentioning
confidence: 99%
“…A recent meta-analysis of 35 publications involving 429 583 pregnant women identified several important risk factors for asthma exacerbations during pregnancy [14 ▪▪ ]. The authors found that increased maternal age (mean difference 0.62, 95% CI 0.11–1.13), obesity (relative risk 1.25, 95% CI 1.15–1.37), smoking (relative risk 1.35, 95% CI 1.04–1.75), black ethnicity (relative risk 1.62, 95% CI 1.52–1.73), multiparity (relative risk 1.31, 95% CI 1.01–1.68), depression/anxiety (relative risk 1.42, 95% CI 1.27–1.59), moderate–severe asthma (relative risk 3.44, 95% CI 2.03–5.83, versus mild) and severe asthma (relative risk 2.70, 95% CI 1.85–3.95) were associated with an increased risk of asthma exacerbations during pregnancy.…”
Section: Risk Factors During Pregnancymentioning
confidence: 99%
“…Pregnant women with asthma and obesity are at greater risk of stillbirth, neonatal mortality and preterm birth compared to asthmatic pregnant women with a normal BMI [133]. Maternal obesity increases the risk of asthma exacerbations [28,126,134,135]. Excessive gestational weight gain during the first trimester of pregnancy, particularly of more than 5 kg is associated with an increased risk of asthma exacerbations [136].…”
Section: Obesitymentioning
confidence: 99%
“…In non-pregnant women with asthma, OSA may contribute to poor disease control, and increase the risk for exacerbations [26,151]. Maternal obesity is an independent risk factor for maternal complications, such as exacerbations during pregnancy, but also a major risk factor for OSA [28]. Also, patients with CRS have an increased risk for OSA [152,153].…”
Section: Obstructive Sleep Apneamentioning
confidence: 99%
See 1 more Smart Citation
“…Asthma exacerbation during pregnancy mostly occurs in the second trimester ( 85 ). A recent meta-analysis has shown that old gestational age, obesity, smoking, multipara, anxiety and depression, and moderate to severe asthma increase the risk of asthma exacerbation during pregnancy ( 86 ). Other risk factors for asthma exacerbation during pregnancy include poor compliance to medication, respiratory viral infection, and rapid weight gain during pregnancy ( 85 , 87 ).…”
Section: Incidence and Management Of Asthma In Different Age Groups A...mentioning
confidence: 99%